Retraction notice to "HIF-1α mediates tumor-nerve interactions through the up-regulation of GM-CSF in pancreatic ductal adenocarcinoma" [Cancer Lett. 453 (2019) 10–20]. (1st April 2023) - Wang, Haotian; Jia, Rujiang; Zhao, Tiansuo; Li, Xin; Lang, Mingxiao; Lan, Chungen; Wang, Hongwei; Li, Zengun; Zhou, Bodong; Wu, Liangliang; Sun, Yan; Wang, Xiuchao; et al.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief and Authors. Following concerns raised in the public domain, the authors contacted the journal to request the retraction of the article. Sections of panels from various figures appear similar to each other, particularly panels from Figs. 3G, 5B and 3G and 5F, 3F, S4D, S5D, S5C and S10C, as well as S10E.